Patellar Groove Replacement in a Cat - Jaworski, Janusz; Krukowski, Maciej; Gosling, Mark; Burton, Neil (VCOT Open, 2022)
The aim of this study was to report patellar groove replacement in a 6-year-old domestic short hair cat with chronic unilateral pelvic limb lameness and severe femoro-patellar osteoarthritis due to medial patellar luxation. This study is a case report. Computed tomographic scan of the affected limb revealed marked periarticular osteophytosis, medial trochlear ridge erosion, marked flattening of femoral trochlea, ectopic pseudo-trochlear groove, and medial patellar luxation. Femoral trochlear ostectomy with patellar groove replacement, release of the medial fibrocartilage, partial parasagittal patellectomy, and lateral tibial tuberosity were performed. Clinical review and radiographs performed 53 days post-surgery revealed no complications and substantial decrease in lameness. Thirteen months postoperatively the cat scored 2/72 on the Feline Musculoskeletal Pain Index questionnaire by the owner, indicating good mobility, minimal discomfort, and good quality of life. As far as the authors are aware, this is the first report of the use of patellar groove replacement in the management of feline medial patellar luxation. Patellar groove replacement, in combination with adjunctive procedures, resulted in a substantial improvement in lameness in this cat with chronic medial patellar luxation and severe femoro-patellar osteoarthritis.
Keywords: feline; medial patellar luxation; patellar groove replacement; CT